The Tendencies of the Development of Cultural Contradictions in the Information Society and Their Effect on the Development of the Educational System in Russia - Taranenko, Natalia Yurievna; Rusetskaya, Elvira Antsasovna; Glaz, Viktor Nikolaevich; Glaz, Yuliya Aleksandrovna; Okorokova, Olga Alekseevna (Journal of History Culture and Art Research, 2018)
The article considers the global information society as a postindustrial development society, culture inherent to it as a science issue and the process of the human’s self-revelation. Different approaches to defining global cultural contradictions in the information society as well as the scenarios of their development are analyzed. Education is one of the leading factors of social and economic development of the global information society. The system of cultural contradictions formed in the global information society and the tendencies of their development affect directly the educational system and act as a basis for the change in the cultural function of education. The changes in the educational values fundamentally alter the view on educational activity in the modern Russian educational system. These changes range from obtaining grounds for professional training to the individual’s ability for self-development, independent development of skills to solve non-standard problems.